New prospects in neutering male animals using magnetic nanoparticle hyperthermia - Jivago, José Luiz P. R. (2021)
Controlling populations of free-roaming dogs and cats poses a huge challenge worldwide. Non-surgical neutering strategies for male animals have been long pursued, but the implementation of the procedures developed has remained limited to date. As submitting the testes to high temperatures impairs spermatogenesis, the present study investigated localized application of magnetic nanoparticle hyperthermia (MNH) to the testicles as a potential non-surgical sterilization method for animals. An intratesticular injection of a magnetic fluid composed of manganese-ferrite nanoparticles functionalized with citrate was administered followed by testicle exposure to an alternate magnetic field to generate localized heat. Testicular MNH was highly effective, causing progressive seminiferous tubule degeneration followed by substitution of the parenchyma with stromal tissue and gonadal atrophy, suggesting an irreversible process with few side effects to general animal health.